A history of charisma - Potts, John, 1959- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2009)
This text traces the history of the word 'charisma', and the various meanings assigned to it, from its first century origins in Christian theology to its manifestations in 21st century politics and culture, while considering how much of the word's original religious meaning persists in the contemporary secular understanding.
Includes bibliographical references (p. 249-258) and index.
Keywords: Geschichte; Charisma (Personality trait) -- History; Pentecostalism -- History; English language -- Etymology; English language -- Word formation; English language -- History; Charisma